The Role of Serum Angiopoietin-Like Protein 4 (ANGPTL-4) and its Gene in Iraq Patients with Type2 Diabetes Mellitus: Case-Control Study - Ali, Aseel; I. Hamzah, Mohammed; Shakir Khudhair, Mahmood (Al-Nahrain Journal of Science, 2021)
ackground Type 2 Diabetes Mellitus is produced by cell failure of pancreatic cells and insulin resistance and is a disorder in which the amount of sugar in the blood is elevated. Angiopoietin-like protein 4 (ANGPTL4) functions as an inhibitor of lipoprotein lipase, a critical enzyme in lipid metabolism. The aim of this study was to explore if the ANGPTL4 gene’s E40K variant and ANGPTL4 serum levels are related to the Body mass index, fasting glucose levels, lipid levels, and glycated hemoglobin. Method 75 people were enrolled in this case-control study, 25 of whom had type 2 diabetes mellitus while the other 50 were healthy control subjects. Fasting blood glucose, Lipid profile, Glycated hemoglobin were estimated by Cobas 111 analyzer, BMI (weight, height) was calculated, angiopoietin-like protein 4 by an enzyme-linked immune sorbent test kit and TaqMan genotyping-based real-time PCR was used to ascertain ANGPTL4 genotypes. The variant was linked to the risk of Type 2 Diabetes Mellitus and parameters used to quantify the variant were identified. Result Patients in the 30-50 age range with type 2 diabetes and those in the same age group who serve as controls. The control group had a lower level of angiopoietin-like protein 4 (ANGPTL4) than the diabetes group. Patients with T2DM had a substantially (p < 0.0001) greater fasting serum Angiopoietin-like protein 4 level than the control group (135.1±6.70) ng/ml and (62.35±6.4) ng/ml, respectively. The diabetes group has significantly higher fasting serum glucose, lipid profile, and glycated hemoglobin compared with non-diabetics. Serum Angiopoietin-like protein 4 was correlated positively with body mass index. (CC,CT,TT) genotypes of the rs2010871 polymorphism There was a significant difference in frequency of the control group (p = 0.0477); however, there was no significant difference in its level of (diabetics, newly diagnosed type 2 diabetic before treatment) p-value (0.7066, 0.5555) respectively Conclusion Serum Angiopoietin-like protein 4 levels are negatively correlated to cholesterol, positively correlated to triglyceride, negatively correlated to HDL, positively correlated to HbA1c, negatively correlated to LDL, negatively correlated to VLDL, negatively correlated to FBS, negatively correlated to BMI. The C>T allele at the ANGPTL4 gene’s rs2010871polymorphic locus was linked to a decreased prevalence of Type 2 diabetes.